THE REPRESENTATION OF INDONESIAN PRESIDENTIAL CANDIDATE IN MEDIA: A CRITICAL DISCOURSE ANALYSIS - Tanto, Trisnowati; Tanusy, Jeanyfer (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
Mr. Prabowo Subianto is often regarded as a controversial figure, both in his military and political career. This research aims to find out Mr. Prabowo Subianto’s representation in one of The New York Times articles entitled “Indonesian General Accused of Kidnapping Is Named Defense Minister”, which was written by Richard C. Paddock in 2019. The article mainly discusses the controversial issue regarding Mr. Joko Widodo’s, the re-elected President of Indonesia, decision to appoint Mr. Subianto, his rival in the presidential election, to be one of his cabinet ministers. In analyzing the topic, van Dijk’s Critical Discourse Analysis, is utilized. Despite the fact that in van Dijk’s CDA there are three levels of analysis, namely the macro, meso, and micro levels, this paper is limited to the micro level only, as this focuses more on unveiling a more specific and detailed portrayal of Mr. Subianto’s representation in the newspaper article. In the microstructure analysis, three linguistics tools are employed, namely actor description, level of description, and rhetoric. The research applies the descriptive qualitative method as well as the library research method. The findings consistently show the negative representation of Mr. Subianto in the macrostructure, microstructure and superstructure analyses.